ONE WAY TO CHILDHOOD: AN EDUCATION AS TIME AND SPACE FOR MULTIPLE EXPERIENCES (Fiep Bulletin - online, 2013)
The objective of this research work is to analyze how the cultures of childhood are understood in the context of early childhood education and worked as are the four main structure of these cultures, known as the second Sarmento (2004): interactivity, fun, fantasy to reality, and repetition. The interest in researching this topic arose from the fact that the actors know little about the school children's cultures and research can contribute to that new concepts are socialized and even incorporated by educators of children. The methodology is qualitative in nature, characterizing himself as research-action. This research is likely social and empirical basis, being designed and carried out in close association with the settlement of a collective problem and in which the researcher and participants representative of reality are involved in cooperative or participatory. The research is being done with educators from two municipal schools of Children's Education City of Presidente Prudente and several advances have been effective. In recent evaluations, the educators of the school, which had emphasized the benefits from this work, because designs are being reviewed and actions have generated changes that reflect the way in practice qualitative education and training of children. It is expected as a result, expanding the production of knowledge and consistent with scientific rigor, which promote the development of codes and notes that can assist in qualitative changes in the educational practices of the participants in the research and to support other professionals for this type education.
Keywords: Childhood; cultures; training.